2016
DOI: 10.1021/acsnano.6b03443
|View full text |Cite
|
Sign up to set email alerts
|

High Luminescence Efficiency in MoS2 Grown by Chemical Vapor Deposition

Abstract: The user has requested enhancement of the downloaded file.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
153
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(170 citation statements)
references
References 41 publications
13
153
3
1
Order By: Relevance
“…36 In fact, the activity of those defect states can be diminished using a nonoxidizing organic superacid, such as bis(trifluoromethane)sulfonimide, providing a drastic enhancement of the PL emission. 40,41 Thus, to reaffirm that the decreased PL intensity in our hexagonal crystal originates from defects, we dipped the samples in a bis(trifluoromethane)sulfonimide solution for 1 h and found that the PL emissions drastically recovered in both the triangles and hexagons. The degree of enhancement was more severe in the hexagon than the triangle, implying that more defect states initially existed in the hexagonal MoS 2 crystals.…”
Section: Synthesis Of Multi-stacked Mos 2 Crystalsmentioning
confidence: 58%
“…36 In fact, the activity of those defect states can be diminished using a nonoxidizing organic superacid, such as bis(trifluoromethane)sulfonimide, providing a drastic enhancement of the PL emission. 40,41 Thus, to reaffirm that the decreased PL intensity in our hexagonal crystal originates from defects, we dipped the samples in a bis(trifluoromethane)sulfonimide solution for 1 h and found that the PL emissions drastically recovered in both the triangles and hexagons. The degree of enhancement was more severe in the hexagon than the triangle, implying that more defect states initially existed in the hexagonal MoS 2 crystals.…”
Section: Synthesis Of Multi-stacked Mos 2 Crystalsmentioning
confidence: 58%
“…The high absorbance values underline the strong light matter interaction of SC-TMDs even in the monolayer limit with a thickness of less than 1 nm as it has been reported by several theoretical and experimental studies, too [14,22,26,27,[45][46][47][48]122,124,128,130] . The sizeable reduction of the absorbance for monolayers on a substrate points to the fact that the optical response can be significantly altered just by modification of substrate or environment by dielectric engineering and screening effects [38,62,63,65,74,89,127,[131][132][133] . The strong influence of the environment on the light-matter interaction of atomically thin semiconducting membranes motivates a great potential not only for sensing applications, but also for novel device architectures with precisely tailorable optical properties.…”
Section: From the Extinction Coefficient In The Visible Range Displaymentioning
confidence: 99%
“…SC-TMDs possess outstanding electronic [6,7,16,19,20] , excitonic [21][22][23][24][25][26][27] , mechanical [28] as well as fascinating spin-and valley [29][30][31][32] properties. SC-TMDs feature also various exotic properties including as single photon emission in WSe2 at low temperatures [33][34][35][36][37] , photoluminescence efficiency with near unity quantum yield achieved by chemical treatment of sulfur-based SC-TMDs [38,39] , layer-dependent superconductivity in highly doped MoS2 [40][41][42][43][44] to name just a view. In addition, more technology relevant characteristics are outstanding FET performance [16] , high sunlight absorbance of up to 15% in the visible range [45][46][47] , ultrahigh photosensitivity [48][49][50] , catalytic activity [51,52] and photocatalytic stability in aqueous electrolytes [53] making the material not only interesting to replace silicon in electronics but also as photo-catalyst e.g.…”
Section: General Introduction To 2d Materials and In Particular Semicmentioning
confidence: 99%
“…In monolayer MoS 2 (thickness ≈0.6 nm), the band gap becomes direct with a width of 1.8 eV. [1] Importantly, to meet the requirements of different applications, properties of MoS 2 and other TMDCs can be tuned by controlling the thickness, [1] doping and alloying, [5][6][7][8] surface modification and functionalization, [9][10][11] strain, [12,13] and by creating heterostructures with other 2D materials. [6,[14][15][16] The appealing properties of TMDCs have led to a wide range of proposed applications.…”
mentioning
confidence: 99%